2009
DOI: 10.1590/s1415-52732009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anemia ferropriva em gestantes brasileiras: uma revisão dos últimos 40 anos

Abstract: A anemia ferropriva é conhecida como uma das principais deficiências nutricionais em todo o mundo e sua ocorrência pode ser observada em diversas populações. Alguns grupos populacionais ainda apresentam altas prevalências de anemia ferropriva, comprometendo diversas funções do organismo. Dentre esses grupos de risco, podem ser citadas as gestantes, que merecem especial atenção devido à sua vulnerabilidade à carência e ao aumento significativo de suas necessidades, que não são acompanhados por aumento suficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
2
16
0
9
Order By: Relevance
“…The results confirmed the increase in the occurrence of anemia with the advance in the gestational period, as observed in several studies, where the prevalences of anemia varied from 3.6% to 23.9% in the first trimester; from 9.2% to 43.9% in the second trimester; and from 10.9% to 52.3% in the third trimester 4 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results confirmed the increase in the occurrence of anemia with the advance in the gestational period, as observed in several studies, where the prevalences of anemia varied from 3.6% to 23.9% in the first trimester; from 9.2% to 43.9% in the second trimester; and from 10.9% to 52.3% in the third trimester 4 .…”
Section: Discussionsupporting
confidence: 91%
“…The total prevalences of anemia found in the city of Maringá-PR both before (12.3%) and after (9.3%) flour fortification were lower than the prevalences of 30 to 40% estimated for pregnant women in Brazil 2 and the data established by a review of articles published in the last 40 years 4 . With regard to categories of epidemiological importance, they are classified as mild, a level defined by prevalences of anemia in pre-school children and pregnant women ranging between 5% and 20%, according to the classification proposed by the World Health Organization (WHO) 1 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The National Survey on the Demography and Health of Children and Women reported that 30% of the women of childbearing age are anemic and that there are no national studies with consistent data about the occurrence of anemia in pregnant women 4 . In a review study, Côrtes et al 5 reported that the prevalence of anemia in Brazilian women on the second trimester of pregnancy varies from 9% to 44%.…”
Section: Introductionmentioning
confidence: 99%